ANALISIS DAYASAING KOMODITI TEMBAKAU RAKYAT DI KLATEN JAWA TENGAH - SAPTANA -; SUPENA FRIYATNO; TRI BASTUTI P. (SOCA: Jurnal Sosial Ekonomi Pertanian, 2004)
Historically tobacco commodities had been interesting as high value commodity sinceHindia Belanda Colonialist. Indonesian government to be continued tobacco developmentimplemented by government estate enterprise (Perusahaan Negara Perkebunan). Tobaccofarm by smallholder estate in Klaten objective to export commodities. Based on the problemin the tobacco commodities system, this paper have objective to : (1) Performance of tobaccoeconomics; (2) Private and social analysis profitability; (3) Comparative and competitiveanalysis; (4) Incentives policy analysis in the tobacco commodities system; (5) To formulatedevelopment perspective on tobacco commodities. Methodological on this paper use PolicyAnalysis Matrix (PAM), especially to analysis competitiveness and impact of divergences.The result to describe that tobacco small holder farming in Klaten have comparative andcompetitive advantage, each to indicate coefficient value of DRC : 0.42-0.65 and PCR : 0.55-0.67. Even though tobacco market especially for export very high distorted, i.e. cukai costhave achieve 30-40 %. So that rural area in Klaten, Central Java more profitable to increasingfor tobacco domestic production compared with import. Policy implication, tobaccoproduction in Klaten can to be continued improvement by specific location of technologydevelopment. The several argument are efficiency of domestic resource use, extensive oflabor absorption, and so to gate some foreign exchange that is scarcity.